2010
DOI: 10.1063/1.3328783
|View full text |Cite
|
Sign up to set email alerts
|

A smoothing monotonic convergent optimal control algorithm for nuclear magnetic resonance pulse sequence design

Abstract: The past decade has demonstrated increasing interests in using optimal control based methods within coherent quantum controllable systems. The versatility of such methods has been demonstrated with particular elegance within nuclear magnetic resonance (NMR) where natural separation between coherent and dissipative spin dynamics processes has enabled coherent quantum control over long periods of time to shape the experiment to almost ideal adoption to the spin system and external manipulations. This has led to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…We also propose to use DL for pulses designed with time‐demanding or advanced techniques. This could be quantum mechanical approaches on multispin systems, applications with very precise control updates, or certain characteristics such as pulse envelope smoothness …”
Section: Discussionmentioning
confidence: 99%
“…We also propose to use DL for pulses designed with time‐demanding or advanced techniques. This could be quantum mechanical approaches on multispin systems, applications with very precise control updates, or certain characteristics such as pulse envelope smoothness …”
Section: Discussionmentioning
confidence: 99%
“…As will be seen in the presented comparative study, however, this monotonicity can get compromised for certain ill parameters. This fact has been studied in more detail by Maday et al 51 and Maximov et al 29 The iteration loop should in this case stop and the previous set of controls may be extracted. The δ and η parameters replace the role ε has in GRAPE.…”
Section: The Krotov-based Approachmentioning
confidence: 99%
“…24 Furthermore, for comparison, we adopted a second-order gradient ascent quasi-Newton algorithm known as Broyden 36 40 recently demonstrated that BFGS has a robust and relatively steep convergence in the later iterations, which may complement the Krotov approach being significantly faster in the first iterations. 24,29 Adapting this strategy, Eitan et al 41 found it worthwhile to combine Krotov with BFGS in relation to quantum control problems. In this work, we have adapted the Krotov-BFGS (multiple control variation of Eitan's approach) for the design of MDRF pulses.…”
mentioning
confidence: 99%
See 2 more Smart Citations